Mecánicas del encuentro: arpones híbridos de las costas de Atacama - Benjamín Ballester (Nuevo mundo - Mundos Nuevos, 2022)
Those objects that pretend to be simple and banal in appearance, often have unsuspected depths, since out of their most obvious function they can hide endless numerous nooks, interstices and secrets. This is the case of the 16th to 19th century iron harpoon from the coast of the Atacama Desert in northern Chile. A sophisticated object assembled from multiple parts, hardly studied and never discussed, its uniqueness is that it possesses a pre-Columbian design combined with European materials. The following paper reveals an unknown find deposited in the British Museum in London, from which a reflection on the role of hybrid harpoons as a mechanism for resolving the technical and cultural tensions produced by the encounter between native residents and European outsiders in a littoral scenario.